2022
DOI: 10.1186/s12875-022-01659-1
|View full text |Cite
|
Sign up to set email alerts
|

HABIT (Health visitors delivering Advice in Britain on Infant Toothbrushing): a qualitative exploration of the acceptability of a complex oral health intervention

Abstract: Background To explore the acceptability of the oral health intervention, HABIT (Health visitors delivering Advice in Britain on Infant Toothbrushing) to parents with young children aged 9–12 months and health visitors. Methods Following the delivery of the universal oral health intervention called HABIT, qualitative semi-structured interviews with parents and focus groups with health visitors were undertaken. Interviews were audio-recorded and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
(30 reference statements)
0
8
0
1
Order By: Relevance
“…Detailed findings from the HABIT early-phase feasibility study are beyond the scope of this paper and are reported in separate publications [35][36][37]. In summary, the feasibility study identified that the HABIT intervention was acceptable to parents, feasible for health visitors to deliver and provided a strong signal of improved PSB behaviours at three months after the intervention.…”
Section: Stage Five: Early-phase Testing Of the Resources To Explore ...mentioning
confidence: 86%
See 3 more Smart Citations
“…Detailed findings from the HABIT early-phase feasibility study are beyond the scope of this paper and are reported in separate publications [35][36][37]. In summary, the feasibility study identified that the HABIT intervention was acceptable to parents, feasible for health visitors to deliver and provided a strong signal of improved PSB behaviours at three months after the intervention.…”
Section: Stage Five: Early-phase Testing Of the Resources To Explore ...mentioning
confidence: 86%
“…We discuss how the findings were incorporated into the study design to ensure the intervention was feasible and deliverable within practice and the research setting. Other papers have focussed on individual aspects of the co-design process, for example the organisational barriers to oral health conversations [20], the feasibility study including the design [35] and mixed methods evaluation [36,37].…”
Section: Complex Behaviour Change Interventions and Co-designmentioning
confidence: 99%
See 2 more Smart Citations
“…Intervention and study design was acceptable to participants and is reported in a separate paper exploring the qualitative findings. 23 In addition, key stakeholders were invited to a research dissemination event held in Bradford in which preliminary findings were presented and feedback sought. Participation included representatives from: Health Visiting and dental teams, Bradford District Care NHS Foundation Trust, Bradford Metropolitan District Council, the British Society of Paediatric Dentistry, Oral Health Strategy Group and Public Health England.…”
Section: Methodsmentioning
confidence: 99%